2015
DOI: 10.5811/westjem.2015.2.23546
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Why Patients Return to the Emergency Department after Mild Traumatic Brain Injury within 72 Hours

Abstract: IntroductionAlthough there are approximately 1.1 million case presentations of mild traumatic brain injury (mTBI) in the emergency department (ED) each year, little data is available to clinicians to identify patients who are at risk for poor outcomes, including 72-hour ED return after discharge. An understanding of patients at risk for ED return visits during the hyperacute phase following head injury would allow ED providers to develop clinical interventions that reduce its occurrence and improve outcomes.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 15 publications
2
18
1
Order By: Relevance
“…In conflict with our study, male gender was reported to be a positive predictor for ED revisits within 72 hours of discharge. 10 , 13 , 18 It may not be possible to compare our findings with those of these studies due to methodological issues, since Ganti et al 13 studied specific population, patients with mild traumatic brain injury. Ahmed et al 19 studied patients with sickle cell disease.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In conflict with our study, male gender was reported to be a positive predictor for ED revisits within 72 hours of discharge. 10 , 13 , 18 It may not be possible to compare our findings with those of these studies due to methodological issues, since Ganti et al 13 studied specific population, patients with mild traumatic brain injury. Ahmed et al 19 studied patients with sickle cell disease.…”
Section: Discussionmentioning
confidence: 89%
“…The ED revisit within 72 hours has been widely reported in earlier studies, and its rate depends on the chronic disease status and the cultural background. 6 12 The rates of 72-hour ED revisits may depend on age, 10 , 11 gender, 10 , 13 disease categories, 6 – 8 , 12 medical errors, 7 , 8 patients, 7 and doctors. 7 Although data regarding ED revisits within 72 hours can be used to implement changes and modifications to improve the electronic medical record database, the rate of revisits to the ED within 72 hours has not been documented among adults with chronic diseases in Saudi Arabia, particularly in our center.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, this might lead to another clinical problem. Intracranial hemorrhage is associated with increased incidence of postconcussion syndrome and postconcussion headache [39,40]. Treatment is available for these patients, but if they are not identified by emergency head CT, another means of identifying them is necessary so they can be offered treatment [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic brain injury (TBI) accounts for over 1 million US emergency department visits annually [1], 275,000 civilian hospitalizations [2] and 21,000 military [3] injuries. Traumatic brain injury can have lasting consequences with neurocognitive deficits [4][5][6][7], post concussive symptoms [8][9][10], and repeat return visits to the emergency department [11].…”
Section: Introductionmentioning
confidence: 99%